(untitled) (Bulletin KNOB, 1990)
Very little is known on the cause of death and the funeral of Duke Karel van Gelre or Karel van Egmond according to his family name. The restoration of the Church of Eusebius in 1963 meant preservation and restoration of his tomb and vault. Sources with respect to his interment have been actualized. To prevent difficulties the Duke’s death on the 30th of June 1538 had been kept a secret. With the exception of the town of Arnhem Van Egmond was no longer popular to the subjects of the Dutch region Gelderland. Already during his life the Duke had been succeeded by Willem van Kleef. His embalmed intestines were carried to the cloister of Monnikenhuizen and the heart to the Church of the Franciscan friars at Arnhem. On the request of the citizens of Arnhem after a solemn funeral the rest of Van Egmond’s body was buried in a vault below the main choir of the Church of Eusebius. His Early Renaissance tomb (1540), which had been removed to the southern ambulatory, is one of Holland’s finest examples. After the demolition of the Church of the Franciscan friars in 1805 the embalmed heart in a leaden box was placed at the mortal remains in the vault of the Church of Eusebius. Opening Karel van Gelre’s burial chamber one found two mouldered wooden coffins one of these containing a shock of sandy hair. The skull possessed an almost triangular bone to which at the time superstitious attached the force of curing epilepsy. At the restoration of the tomb in 1911 the burial chamber has been opened again. The leaden box in one of the coffins turned out to be stolen by desecrators. Together with the box containing the Duke’s embalmed heart the remaining bones stored in a small leaden box were placed into the cellar again. At the 1963 restoration the mortal remains of Karel van Gelre were reburied, provided with a leaden case and charter mentioning all of the tomb’s openings. From that moment on the burial chamber could be visited.